2011
DOI: 10.1557/opl.2011.1018
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nanodiamond – A Novel Nanomaterial forIn VivoApplications

Abstract: Fluorescent nanodiamonds (FNDs) with a size in the range of 10 – 100 nm have been produced by ion irradiation and annealing, and isolated by differential centrifugation. Single particle spectroscopic characterization with confocal fluorescence microscopy and fluorescence correlation spectroscopy indicates that they are photostable and useful as an alternative to far-red fluorescent proteins for bioimaging applications. We demonstrate the application by performing in vivo imaging of bare and bioconjugated FND p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…263 It was found that the NDs entered the food vacuoles of the microorganisms and were excreted later on. 265 It was found that for both organisms, NDs could be delivered to the embryos of the next generation providing excellent fluorescence properties for in vivo imaging. The toxicity of NDs for the observed microorganisms was low, but nevertheless significantly larger than as previously reported for in vitro cell cultures.…”
Section: Nanodiamondsmentioning
confidence: 99%
See 1 more Smart Citation
“…263 It was found that the NDs entered the food vacuoles of the microorganisms and were excreted later on. 265 It was found that for both organisms, NDs could be delivered to the embryos of the next generation providing excellent fluorescence properties for in vivo imaging. The toxicity of NDs for the observed microorganisms was low, but nevertheless significantly larger than as previously reported for in vitro cell cultures.…”
Section: Nanodiamondsmentioning
confidence: 99%
“…The same authors followed up the latter work by utilizing bare and bioconjugated NDs in C. elegans and zebrafish. 265 It was found that for both organisms, NDs could be delivered to the embryos of the next generation providing excellent fluorescence properties for in vivo imaging. In a study from 2012, Igarashi et al studied the application of fluorescent NDs as imaging probes in vivo in C. elegans and mice.…”
Section: Nanodiamondsmentioning
confidence: 99%